Patient-reported outcome measures in children, adolescents, and young adults with palliative care needs—a scoping review - Heidi Holmen; Anette Winger; Simen A. Steindal; Kirsti Riiser; Charlotte Castor; Lisbeth Gravdal Kvarme; Kari L. Mariussen; Anja Lee (BMC Palliative Care, 2023)
Abstract Background Measuring outcomes facilitates evaluation of palliative services for children, adolescents, and young adults (CAYAs) with life-limiting and/or life-threatening (LL/LT) conditions. Implementation of patient-reported, proxy-reported, or patient-centered outcome measures (hereafter PROMs) is recommended to ensure palliative services. The purpose of this scoping review was to provide an overview of PROMs relevant for CAYAs living with LL/LT conditions eligible for pediatric palliative care (PPC). Methods Arksey and O’Malley’s 6-stage scoping review framework was used to guide the review. The identified citations had to report on PROMs in any context including CAYAs with LL/LT conditions up to 25 years of age. A systematic search of Medline, EMBASE, CINAHL, APA PsycInfo, Health and Psychosocial Instruments, and AMED took place in January 2021 and was updated in June 2022. Citations were screened independently by pairs of researchers. The scoping review protocol was registered, and peer-review published. Results Of 3690 identified citations, 98 reports were included, of which the majority were from Western countries and about PROMs in CAYAs living with cancer or organ failure. A total of 80 PROMs were identified, assessing a range of phenomena, where quality of life and symptoms (especially pain) during the stage of ongoing care were the most frequent. There were only a few reports about outcome measures at time of diagnosis or in end-of-life care. CAYAs self-reported on the PROMs or collaborated with their parents in about half of the reports, while the remaining had proxies answering on behalf of the CAYAs. In the identified reports, PROMs were used to characterize a sample through cross-sectional or longitudinal research, and less often to assess effects of interventions. Conclusion The identified PROMs in the CAYA population eligible for PPC is characterized by studies in high-income countries during ongoing care, primarily in patients with cancer or organ failure. More research is needed in patients living with other LL/LT conditions, and during different stages of the disease course, especially at time of diagnosis, during transition to adulthood, and in end-of-life care. This scoping review of PROMs relevant for young patients eligible for PPC may inform future research about patient-/proxy-reported or patient-centered outcome measures in PPC. Trial registration Review registration: ( https://osf.io/yfch2/ ) and published protocol (Holmen et al. Syst Rev. 10:237, 2021).